Animal domestication in the high Arctic : Hunting and holding reindeer on the I͡Amal peninsula, northwest Siberia - Anderson, David G.; Harrault, Loïc; Milek, Karen B.; Forbes, Bruce C.; Kuoppamaa, Mari; Plekhanov, Andreĭ V. (Journal of Anthropological Archaeology, 2019)
The primary funding for this study was provided by the ESRC ES/M011054/1 “JPI Climate: Social-Ecological Transformations: HUMan-ANimal Relations Under Climate Change in NORthern Eurasia” held at the University of Aberdeen, within the Nordforsk network HUMANOR at the University of Lapland (Decision #291581). Additional support came from the Academy of Finland project “Resilience in Social-Ecological Systems of Northwest Eurasia” (RISES, Decision #256991). We are grateful to a large number of people for making this ambitious fieldwork possible. We are thankful to Natal'i͡a Fedorova and Andreĭ Gusev of the Scientific Centre of Arctic Studies for sharing their knowledge of the history of I͡Amal. We are extremely thankful to Konstantin Oshchepekov for expertly organizing all of the logistics connected with our fieldwork in I͡Amal. The geoarchaeological fieldwork would not have been possible without the help of Julia Kremkova. We are grateful to Bill Fitzhugh, Sven Haakanson, Pavel Kosint͡sev, Nata Panova and Andreĭ Golovnëv for sharing their first-hand accounts of earlier excavations. We are also grateful to Bryan Gordon, Vladimir D'i͡achenko, Rob Losey, Tanya Nomokonova, Yuka Oishi, Elena Volzhanina, Dmitry Arzyutov, Zoya Ravna and Roza Laptander for commenting on aspects of earlier drafts. We are very grateful for the helpful and constructive comments of an anonymous reviewer. Peer reviewed